Propagation of Electrical Trees under the Influence of Mechanical Stresses: A Short Review - Danikas, M.; Papadopoulos, D.; Morsalin, S. (Engineering, Technology & Applied Science Research, 2019)
The present paper deals with the phenomenon of electrical treeing in solid insulation, under the influence of mechanical stresses. In this short review, it is indicated that mechanical stressing can affect the propagation of electrical trees and –depending on whether it is tensile or compressive- it can facilitate (or render more difficult) the breakdown. In aged insulating materials, electrical trees can appear very quickly and can lead to breakdown.